Analysis of the Increase of Transformer Power Losses due to the Operation of Unbalanced Nonlinier Loads - Rinas, I Wayan; Suartika, I Made; Pemayun, Anak Agung Maharta (Journal of Electrical, Electronics and Informatics, 2018)
Non-linear loads are the source of harmonic current for electric utilities. The high level of harmonics greatly affects the increase of losses of electrical power (losses). The quality of electric power is determined by the parameters of power losses that occur in the transformer due to harmonic distortion. In this research will be analyzed THD from result of measurement and simulation in accordance with IEEE 519-2014 standard, power loss analysis on transformer before and after. Harmonics, the impact is increased due to unbalanced linear currents.